Preliminary study of oxidative stress biomarkers and trace elements in North Sea Harbour Seals. (February 2021) - Gismondi, Eric; Daneels, Lucienne; Damseaux, France; Lehnert, Kristina; Siebert, Ursula; Das, Krishna
Abstract: This preliminary study investigated the potential correlations between trace elements (mercury, zinc, cadmium, copper, selenium, lead, nickel, chromium, lithium and vanadium) concentrations, measured in red blood cells, and oxidative stress biomarkers (total thiols, total glutathione, total and selenium-dependent glutathione peroxidases, triglycerides, malondialdehyde) assessed in the respective serum, in males and females P. vitulina, sampled in the Wadden Sea in spring and autumn 2015. Only concentrations of total mercury and zinc showed significant differences by sex, and only lipid peroxidation was different by season. Moreover, significant positive and negative correlations were observed between biomarkers (triglycerides, thiols, malondialdehyde, glutathione) and trace element concentrations (copper, lead, mercury, nickel, zinc). These findings suggest that the studied biomarkers could be useful for the assessment of oxidative stress in harbour seals exposed to trace elements, but further research with larger sample sizes is needed to better understand their specific associations. Graphical abstract: Unlabelled Image Highlights: Trace elements and biomarkers measured in P. vitulina blood cells and serum Sex- or season differences observed only for mercury and zinc concentrations No significant difference in biomarkers according to sex and season Triglyceride and lipoperoxidation positively correlated to copper, lead and nickel Total thiols and GSH negatively correlated to Pb and females T-Hg, respectively